Two-year cycle of vendace (Coregonus albula) in Pyhäjärvi, SW Finland: evidence for asymmetric competition between adults and juveniles - Sarvala Jouko; Helminen Harri (FINNISH ZOOLOGICAL BOTANICAL PUBLISHING BOARD, 2022)
Long-term monitoring of the planktivorous vendace (Coregonus albula) in Pyhajarvi, a lake in SW Finland, revealed periods characterised by different types of population regulation. In 1971-1989, the vendace stock was strong and exhibited a two-year cycle. In 1990-1999, extreme weather conditions and predation resulted in recruitment failures, after which overfishing kept year-classes small. From 2000 onwards, the two-year oscillations were re-established at a lower level. Here, we show that the two-year cyclicity prevalent in the 1980s was consistent with the hypothesis of asymmetric competition between adults and juveniles. Food consumption by juveniles of strong year-classes retarded growth and weakened condition of the co-occurring adults, resulting in less abundant year-classes. In 2000-2018, the role of intraspecific competition diminished due to interspecific competition from increased populations of other planktivorous fish, preventing vendace from attaining higher abundance. Elevated temperature probably confounded the effects of competition, but its direct role was masked by simultaneous gradual eutrophication and fish assemblage changes.